Mine Site Restoration - Maximisation of Topsoil in Restoration of Semi-arid Lands - Lison, Christine Anne (Curtin University, 2020)
This thesis examined the physical and chemical properties of soil mixes incorporating 25%, 50%, 75% and 88% waste rock and tested the influence of these properties on plant growth and development and early seedling growth. Results of the analysis indicate that increasing waste rock content causes an increase in soil salinity, a decline in soil water content but an improvement in soil water conservation. This study paves the way for efforts to optimise restoration practices.